2012
DOI: 10.1111/j.1460-9592.2012.03899.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol–remifentanil intravenous anesthesia and spontaneous ventilation for airway foreign body removal in children with preoperative respiratory impairment

Abstract: Propofol-remifentanil TIVA and spontaneous ventilation are effective and safe techniques to manage anesthesia during airway FB removal in children with preoperative respiratory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…[13,25,26] There is no consensus on the use of spontaneous or controlled ventilation during anaesthesia for bronchoscopies. In our study, the bronchoscopies were performed under general anaesthesia with inhalational induction and controlled ventilation in all children.…”
Section: Discussionmentioning
confidence: 99%
“…[13,25,26] There is no consensus on the use of spontaneous or controlled ventilation during anaesthesia for bronchoscopies. In our study, the bronchoscopies were performed under general anaesthesia with inhalational induction and controlled ventilation in all children.…”
Section: Discussionmentioning
confidence: 99%
“…as a bolus of 4 mg kg 21 followed by infusion of 1-2 mg kg 21 h 21 ; the bolus was given over 10 min to prevent haemodynamic depression. In Group RP, remifentanil was started at 0.05 mg kg 21 min 21 and was adjusted in 0.05 mg kg 21 min 21 increments to titrate a 50% reduction in the baseline respiratory rate. Lidocaine (1%; 2 mg kg 21 ) was sprayed on the oropharynx, supraglottic, and glottic structures, and into the trachea via a direct laryngoscope.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review in 2010 showed that the mortality rate among children with aspirated foreign bodies was 0.4%. In China, tracheobronchial foreign body aspiration in children is mostly due to dietary and feeding customs . In recent years, the incidence has declined due to health education, but still remains high among children in rural areas.…”
Section: Introductionmentioning
confidence: 99%